Structural optimisation of random discontinuous fibre composites: Part 2 - case study - Qian, C.C.; Harper, L.T.; Turner, T.A.; Warrior, N.A. (Elsevier, 2015)
This is the second paper in a two part series presenting the development of a stiffness optimisation algorithm to intelligently optimise the fibre architecture of discontinuous fibre composites. A Multi-Criteria Decision Making (MCDM) strategy is used to select parameters associated with the fibre architecture, to produce components that satisfy stiffness, cost and mass criteria. The model has been successfully demonstrated using an automotive spare wheel well geometry, which shows that a highly optimised discontinuous fibre composite solution can compete against a continuous fabric counterpart in terms of specific stiffness, whilst presenting an opportunity for significant cost reduction. This could potentially lead to the application of composite materials into new areas where cost has previously been prohibitive.